An improved method of recovery factor estimation for low-permeability carbonate reservoirs. (3rd June 2022) - Liu, Guangwei; Yang, Li; Yang, Baoquan
Abstract: At present, there are limited empirical formulas for recovery factor estimation of carbonate reservoirs in the early stage of development. An improved recovery factor estimation method is established in this paper combining with displacement efficiency, sweep coefficient, well pattern coefficient, utilization factor, and reservoir connectivity coefficient. Among them, the utilization factor and connectivity coefficient is firstly proposed and established by derivation and reservoir simulation considering the characteristics of low-permeability carbonate reservoirs. The method is applied to M oilfield, and the estimation results are compared with other empirical formulas and field development calibration results, which shows good estimation accuracy.